The dynamics of empowering women in the post-missionary Church of Christ in Zimbabwe - Masengwe, Gift (HTS teologiese studies, 2024)
The evolution of the Ladies’ Circle into the Mother’s Union in the Church of Christ in Zimbabwe (COCZ) holds great significance in that circles in Africa symbolize collectiveness and consensual decision-making. The Ladies’ Circle emerged as a response by white women influenced by the Victorian Womanhood Cult with regard to the discontent they felt with patriarchy in the church. Black women supported white female missionaries in leadership roles, when they (black women), continued to face oppression due to (white and black) male resistance to change, as well as fear of losing male-privileges. Empirical evidence in the COCZ suggests that black women in Zimbabwe made significant progress in the secular world compared to their progress in church. This study uses a Critical Discourse Analysis (CDA) as a theoretical framework to examine how the transformation of the Ladies’ Circle into the Mothers’ Union empowered African women to deal with their own oppression. It aims to understand how white women overcame restrictive Victorian norms and the Womanhood Cult, which promoted submissiveness and domesticity as defining aspects of womanhood. The study further notes that inconsistencies in addressing race and gender differences in the church perpetuated the dominance of African men on women within the church. This study thus acknowledges that the Women’s Unions, like the Mothers’ Union, have the potential to empower COCZ women and challenge racial and gender oppression within that church.Contribution: The study reveals that denying women’s involvement in church can have debilitating effects on gender equality in Zimbabwe. The Ladies’ Circle, a platform created by the Church of Christ, provides women with a space for social and religious participation. The intersection of gender, race, and religion used by religious and cultural authorities to control women, call for a re-examination of the COCZ’s theological foundations on these subjects.